Snow removal cools a small dystrophic lake - H. A. Dugan; R. Ladwig; P. Schramm; N. R. Lottig (Limnology and Oceanography Letters)
Abstract Limnological understanding of the role snow plays in under‐ice thermal dynamics is mainly based on studies of clear‐water lakes. Very little is known about the role snow plays in the thermal dynamics of dystrophic lakes. We conducted a whole lake experiment on a small, 8 m deep dystrophic bog lake in northern Wisconsin, where we removed all snowfall over two consecutive winters. Due to weather variability, only 1 year had predominantly black ice. Under these conditions, the lake rapidly cooled in early and mid‐winter, compared to snow covered conditions that insulated the lake from heat loss. The lake also rapidly gained heat in late winter resulting in isothermal conditions well in advance of ice‐off. These results show how water clarity modulates the influence of snow on under‐ice thermal dynamics, which is relevant to futures with snow droughts.